Development and application of an indirect competitive enzyme-linked immunosorbent assay for the detection of p, p ′-DDE in human milk and comparison of the results against GC-ECD - Hongsibsong S. (2014)
1,1-Dichloro-2,2-bis(p-chlorophenyl) ethylene (p,p′-DDE) is the major metabolite of insecticide 2,2-bis(p-chlorophenyl)-1,1,1-trichloroethane (p,p′-DDT) and a persistent organic pollutant (POPs) with concerns regarding its bioaccumulation and persistence in the environment and food chain. In the present study, an indirect competitive enzyme-linked immunosorbant assay (ic-ELISA) specific for the detection of p,p′-DDE is described. In hapten synthesis, 2,2′-bis(4-chlorophenyl)ethanol and glutaric anhydride were used as precursor and spacer arm, respectively. The hapten was then conjugated to bovine serum albumin (BSA) as immunogen for mouse immunization and also conjugated to ovalbumin as coating antigen for ELISA. The developed ic-ELISA was used for detecting p,p′-DDE in human milk samples and validated against the results from conventional gas chromatography-electron capture detection (GC-ECD). Coefficients of variation (%CV) of ELISA were 5.7-10.4% for intra-assay and 10.6-19.6% for interassay variations. The Pearson correlation coefficient of p,p′-DDE concentrations between ic-ELISA and GC-ECD was r = 0.766, which was in an acceptable range. The results indicate that the developed assay could be an alternative analytical tool for monitoring p,p′-DDE in lipimic matrices such as human milk. © 2011 American Chemical Society.